Verso una nuova archiveconomia: riflessioni sull’evoluzione della disciplina nella transizione dall’analogico al digitale - Stefano Allegrezza (JLIS.it, 2017)
The paper aims at proposing some considerations on the evolution of the discipline of archival economy in the transition from “traditional” to digital archives, focusing in particular on issues related to the use of new prefixes for binary multiples required for correctly estimate the size of digital archives and the capacity of storage systems. In particular, the paper aims at clarifying this particular aspect, which is rarely taken in consideration while it is very important to take it in consideration during the creation of a digital archive. As a consequence, the skills required to archivists who want to deal with digital archives must change and there is the need of a “new” archival economy which combines the traditional topics with the issues related to the management of digital archives.